Hydrofoam and oxygen headspace bioreactors improve cell‐free therapeutic protein production yields through enhanced oxygen transport. (24th October 2020) - Nelson, J. Andrew D.; Barnett, R. Jordan; Hunt, J. Porter; Foutz, Isaac; Welton, Meagan; Bundy, Bradley C.
Abstract: Protein therapeutics are powerful tools in the fight against diabetes, cancers, growth disorders, and many other debilitating diseases. However, availability is limited due to cost and complications of production from living organisms. To make life‐saving protein therapeutics more available to the world, the possibility of magistral or point‐of‐care protein therapeutic production has gained focus. The recent invention and optimization of lyophilized "cell‐free" protein synthesis reagents and its demonstrated ability to produce highly active versions of FDA‐approved cancer therapeutics have increased its potential for low‐cost, single‐batch, magistral medicine. Here we present for the first time the concept of increased oxygen mass transfer in small‐batch, cell‐free protein synthesis (CFPS) reactions through air‐water foams. These "hydrofoam" reactions increased CFPS yields by up to 100%. Contrary to traditional protein synthesis using living organisms, where foam bubbles cause cell‐lysis and production losses, hydrofoam CFPS reactions are "cell‐free" and better tolerate foaming. Simulation and experimental results suggest that oxygen transfer is limiting in even small volume batch CFPS reactors and that the hydrofoam format improved oxygen transfer. This is further supported by CFPS reactions achieving higher yields when oxygen gas replaces air in the headspace of batch reactions. Improving CFPS yields with hydrofoam reduces the overall cost of biotherapeutic production, increasing availability to the developing world. Beyond protein therapeutic production, hydrofoam CFPS could also be used to enhance other CFPS applications including biosensing, biomanufacturing, and biocatalysis.